RUVBL proteins are involved in plant gametophyte development. (27th February 2023) - Dvořák Tomaštíková, Eva; Yang, Fen; Mlynárová, Kristína; Hafidh, Said; Schořová, Šárka; Kusová, Alžbeta; Pernisová, Markéta; Přerovská, Tereza; Klodová, Božena; Honys, David; Fajkus, Jiří; Pecinka, Ales; et al.
SUMMARY: The proper development of male and female gametophytes is critical for successful sexual reproduction and requires a carefully regulated series of events orchestrated by a suite of various proteins. RUVBL1 and RUVBL2, plant orthologues of human Pontin and Reptin, respectively, belong to the evolutionarily highly conserved AAA + family linked to a wide range of cellular processes. Previously, we found that RUVBL1 and RUVBL2A mutations are homozygous lethal in Arabidopsis. Here, we report that RUVBL1 and RUVBL2A play roles in reproductive development. We show that mutant plants produce embryo sacs with an abnormal structure or with various numbers of nuclei. Although pollen grains of heterozygous mutant plants exhibit reduced viability and reduced pollen tube growth in vitro, some of the ruvbl pollen tubes are capable of targeting ovules in vivo . Similarly, some ruvbl ovules retain the ability to attract wild‐type pollen tubes but fail to develop further. The activity of the RUVBL1 and RUVBL2A promoters was observed in the embryo sac, pollen grains, and tapetum cells and, for RUVBL2A, also in developing ovules. In summary, we show that the RUVBL proteins are essential for the proper development of both male and particularly female gametophytes in Arabidopsis. Significance Statement: We show that RUVBL1 and RUVBL2, plant orthologues of human Pontin and Reptin, are essential for the proper development of both male and especially female gametophytes in Arabidopsis.